Parody in the Epoch of Remake - Belovodskaja, Anastasia (Respectus Philologicus, 2006)
The article focuses on the investigation of parody in the context of contemporary cultural space, more specific, in relation to the apparent prevalence of remakes in so-called "products of the creative process". Therefore, the parody and the remake, while the difference between them lies in the fact that the parody is an ironical alteration of specific works, are analysed from the point of view of a certain type of speech act (game) and its perlocutive function. The source of investigation is works of eminent contemporary writers (e. g., B. Akunin) and anonymous parodies found in humorous Internet portals. Moreover, the phenomenon of the parody is analysed in a broader context, i.e. examples of contemporary political life, mass media, etc. The article claims that not the beginning of the game conditioned by the postmodern attitude of the epoch is realised in the phenomenon called pastiche but a certain way of conceiving the world, which manifests as a protest against the declared system of values and general attitudes.